2009
DOI: 10.1063/1.3103788
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer between laser beams crossing in ignition hohlraums

Abstract: The full scale modeling of power transfer between laser beams crossing in plasmas is presented. A new model was developed, allowing calculations of the propagation and coupling of pairs of laser beams with their associated plasma wave in three dimensions. The complete set of laser beam smoothing techniques used in ignition experiments is modeled and their effects on crossed-beam energy transfer are investigated. A shift in wavelength between the beams can move the instability in or out of resonance and hence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…1). Increasing the wavelength separation ∆λ = λ inner − λ outer leads to energy transfer from the outer to the inner beams, which increases the energy balance towards the hohlraum waist and leads to a more prolate implosion symmetry [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…1). Increasing the wavelength separation ∆λ = λ inner − λ outer leads to energy transfer from the outer to the inner beams, which increases the energy balance towards the hohlraum waist and leads to a more prolate implosion symmetry [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…For CBET, ref. [19] showed the gain per speckle for any pair of quads is 1 in NIF hohlraum conditions, and speckle effects can be neglected. A post-processing version of our CBET model [20], coupled to "high-flux model" hydrodynamics described below, has been validated against NIF shape data during the early-time picket [21], as well as peak power when the power or wavelength shifts are not too high [22].…”
mentioning
confidence: 99%
“…Ref. [19] showed this is appropriate for NIF's polarization scheme. χ j is species j susceptibility,…”
mentioning
confidence: 99%
“…Crossed-beam energy transfer (CBET) [8][9][10] has been identified as a source of reduced laser absorption in direct-drive experiments [11]. Laser light that is transmitted around the target can interact with the central region of incident beams to scatter light from the Mach-1 surface, reducing the ontarget absorbed energy.…”
Section: Crossed-beam Energy Transfermentioning
confidence: 99%
“…a e-mail: rmcc@lle.rochester.edu This is an Open Access article distributed under the terms of the Creative Commons Attribution License 2.0, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Crossed-beam energy transfer (CBET) [8][9][10] has been shown to be important in direct-drive experiments [11]. Simulations and experiments have shown that reducing the laser beam's diameter relative to the target diameter improves the laser-target coupling, increasing the implosion velocity.…”
Section: Introductionmentioning
confidence: 99%